Detecção de adulteração de café torrado e moído com cevada pelo perfil cromatográfico de voláteis - Rafaelcosta dos Santos Oliveira (2007)
The objective of this work was the characterization of the volatile profile of roasted coffee and barley by gas chromatography/mass spectrometry, aiming at the discrimination and detection of adulteration of roasted coffee with roasted barley. Also, investigative tests were performed with commercial roasted coffee and roasted barley samples acquired fromlocal markets and from the Coffee Industry Union of Minas Gerais (SINDICAFÉ-MG). The samples acquired from SINDICAFÉ-MG were suspected to be adultered/contaminated. Collection of the volatile fraction was performed by producing the headspace and extracting/concentrating the volatiles by solid phase micro-extraction (SPME). The performances of three different SPME fibers (CAR/PDMS, PDMS/DVB, PDMS/DVB/CAR)were evaluated, with the triple-phase fiber being selected for this work due to the fact that it extracted more volatile components from the roasted barley headspace, that were not present in roasted coffee headspace, than the other fibers. Multivariate statistical techniques, such as Principal Component Analysis (PCA) and Cluster Analysis, wereemployed in the analysis of the chromatographic profile results. Such techniques demonstrated to be suitable for characterization and differentiation of laboratory roasted coffee and roasted barley, and their respective commercial products. The multivariateanalysis allowed for the differentiation between pure roasted coffee and pure roasted barley, and also between coffee samples presenting distinct roasting degrees. The capability of differentiation between roasting degrees by the chromatographic volatile profile was also observed for roasted barley. Commercial roasted coffee samples, bothwith and without ABIC Quality Seal, and commercial roasted barley samples, were differentiated from coffee and barley samples roasted in the laboratory and the differences were attributed to the different processing conditions. The presence of roasted barley wasnot detected in the coffee samples suspected to be adultered.